185 3-Tesla Magnetic Resonance Imaging Track Density Imaging to Identify Thalamic Nuclei for Functional Neurosurgery. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Shepherd, Timothy M.; Chung, Sohae; Glielmi, Christopher; Mogilner, Alon Y.; Boada, Fernando; Kondziolka, Douglas
Abstract: INTRODUCTION: Essential tremor can be treated by thalamic stimulation or ablation of the ventral intermediate nucleus (VIM) with good outcomes [1]. Routine magnetic resonance imaging (MRI) cannot distinguish between thalamic nuclei so targeting is based on anatomic atlas-based coordinates. Diffusion MRI-based track density imaging (TDI) can better depict internal thalamic structure [2], but previously has required high-field MRI or long acquisitions that are not clinically practical. We applied multiband diffusion MRI [3] to enable 3-Tesla (3-T) MRI TDI in patients with essential tremor. METHODS: Six patients with essential tremor underwent standard preoperative MRI with an additional multiband diffusion sequence that used 3-slice acceleration factor, 3-mm isotropic image resolution, whole-brain coverage (45 slices) and 256 diffusion gradient directions (b = 2500 s/mm 2 ) acquired in 11 minutes. TDI data post-processing generated track density and direction-encoded color maps at 500-micron isotropic super-resolution [2]. RESULTS: Combining TDI and multiband diffusion acquisitions resulted in high-quality images of the human thalamus in typical elderly essential tremor patients using 3-T MRI and clinically feasible scan times. Results also were consistent for repeat imaging in the 3 volunteers. TDI with or without direction-encoding demonstrated some of the internal anatomy of the thalamus, but fiber-orientation maps derived from these data (Fig. 1) were preferred by the 2 participating functional neurosurgeons. CONCLUSION: Multiband diffusion acquisition makes TDI-based parcellation of the thalamus feasible in elderly patients with essential tremor using 3-T MRI. This approach provides at least equivalent data to previous diffusion tractography or TDI approaches for thalamus parcellation, but without long scan times or a 7-Tesla MRI system [4-6]. While planning for gamma knife ablation of VIM for these initial 6 patients still relied on conventional methods, future efforts will focus on validation and careful introduction of TDI-derived thalamic maps to actual surgical planning.